Abses Paru pada COVID-19 - Kurniawan, Adi; Khairan, Paramita; Librianty, Nurfanida; Mahrani, Mahrani; Faisal, Hana; Mutmainah, Iffa; Rahmawati, Fitriana Nur; Marwadhani, Sarah Shafa; Adinda, Gadistya Novitri; Sari, Uti Nilam; Prawirohardjo, Pukovisa (Majalah Kedokteran Indonesia, 2020)
Objective: COVID-19 is a new emerging disease since December 2019 that later was announced by WHO as a global pandemic. Radioimaging appearance of COVID-19 is varied yet dominantly showed as a ground glass appearance in CT-imaging. Lung abscess in COVID-19 is an extremely rare case, therefore it needs further discussion. Method: We report a 39 year-old male patient of COVID-19 with lung abscess.Result: This case report describe a COVID-19 patient who showed a very rare clinical manifestation; lung abscess. The patient showed negative result of TB molecular test. Chest tube insertion procedure was performed in this patient who showed an improvement after abscess being drained. Conclusion: Lung abscess may occur in COVID-19. Abscess drainage procedure may improve clinical condition of COVID-19 patient.